Moralność społeczna młodych ludzi w Anglii i Walii - Kay, William (Horyzonty Wychowania, 2017)
Five factors or agencies leading to the formation of social or personal morality in young people are identified. These are churches, schools, families, communities and the similar impacts of militarisation and industrialisation. The influence of these agencies or factors are surveyed in relation to Britain in the 19th and 20th centuries. There is a discernible weakening of each influence apart from that of schools but, even here, the government’s main concern is not with moral education.